Visual Traces of Majapahit: The Transformation of Artifacts into Contemporary Batik - Setyawan Setyawan; Apika Nurani Sulistyati; Darwoto Darwoto; Alfi Yusrina Farikha (Javanologi: International Journal of Javanese Studies, 2025)
This research aims to trace and reinterpret the visual heritage of Majapahit through a visual anthropology approach as the basis for creating contemporary batik motifs. Majapahit artifacts, such as reliefs, pottery, and architectural ornaments, should not merely be viewed as archaeological objects, but as symbolic representations that record the value systems, cosmology, and aesthetics of bygone societies. Through a process of visual exploration and design reinterpretation, this research reveals how the forms, textures, and narratives embodied in these artifacts can be transformed into new visual elements in modern batik. This approach combines qualitative methods with visual analysis and ethnographic reflection on the motif design process. The results of this research shows that the transformation of Majapahit artifacts into contemporary batik not only enriches aesthetic innovation but also serves as a medium for dialogue between the past and the present. Thus, the resulting batik pieces serve as a living cultural space that revives the visual memory of Majapahit while strengthening the creative identity of the current generation.